A fuzzy logic and game theory based adaptive approach for securing opportunistic networks against black hole attacks. (28th December 2017) - Chhabra, Anshuman; Vashishth, Vidushi; Sharma, Deepak Kumar
Summary: Opportunistic networks (OppNets) are networks that can be used in situations of sparse network connectivity. Strategies for implementing secure transmission of messages in OppNets offer complex and distinctive problems that are wholly different from traditional networks using TCP/IP protocols for data transmission. In this paper, a security protocol named FuzzyPT is proposed which combats black hole attacks in OppNets. The defense mechanism is based on the information extracted from messages in the buffer, potential threat (PT) messages, and fuzzy logic. Fuzziness aids the system in being adaptive by modeling the character of nodes as either benign or malicious. It provides the network with the ability to judge the character of nodes based on relationships between different parameters instead of basing this decision on fixed conditions. FuzzyPT is observed to reduce erroneous decision‐making and decrease the number of false positives and false negatives in the system. An evolutionary game theoretic model is applied, which analyzes the decision‐making ability of relays in choosing varied strategies while forwarding messages. The evolutionary stable state is computed for the protocol, which verifies the proposition that a majority of the relays will cooperate by forwarding messages. The efficiency of the protocol is judged on various grounds such as delivery probability, network overhead ratio, packets dropped, and transmission latency. It is observed that the proposed game theoretic protocol outperforms an existing acknowledge and evolutionary game theory–based security protocol in terms of all the aforementioned performance characteristics. Abstract : In this paper, an evolutionary game theory model based on fuzzy logic is applied to formulate an approach for securing opportunistic networks. The approach, FuzzyPT, outperforms existing mechanisms for a number of different performance metrics.